Health Risk Analysis of Detergent Contamination in Communities on Kodingareng Lompo Island, Makassar City - Marulak Bonaparte Manurung; Tri Edhi Budhi Soesilo; Haryoto Kusnoputranto; I Wayan Koko Suryawan; Imelda Masni Juniaty Sianipar (Universitas Diponegoro, 2022)
Domestic activities in coastal and island communities are one of the factors that can affect the quality and quantity of traditional well water availability. One of the parameters of household wastewater is detergent pollutants. This study aimed to analyze the risk of detergent contamination in drinking water in the community of Kodingareng Lompo Island. This research is a type of quantitative research with a descriptive approach. The method used is the Environmental Health Risk Assessment (EHRA) approach. Based on the examination conducted, the highest concentration was found in drinking water samples 4 and 5, which was equal to 2.98 mg/l. While drinking water sample 2 has the lowest concentration of detergent contamination, which is 0.005 mg/l. The respondents' daily drinking water intake rate is < 2 L/day, 2 L/day and ≥ 2 L/day, with the highest percentage of 31.1% for consumption of 2 L/day. The frequency of detergent exposure in drinking water consumed by respondents, namely > 350 days/year, with a percentage of 84.4%. The most extended duration of exposure, namely 31 - 60 years, with a ratio of 64.4%. The results of ARKL calculations conducted on the concentration of detergent contamination in drinking water showed a high level of risk (RQ > 1) in three respondents and were classified as unsafe for drinking water consumption.